Frequency of enteroparasites in individuals in the municipality of Ponta Grossa - PR (2010-2016) - Zattar Meiga, Marina; Alves De Souza, Juliane; Nunes De Oliveira, Rosimeire; Solano Rocha, Cláudia; Miné, Júlio César (O Mundo da Saúde, 2018)
Among the public health problems in Brazil are the enteroparasitoses, which represent pathologies that weaken the population, being associated with diarrhea and malnutrition, especially in children. The aim of this study was to evaluate the frequency of enteroparasites in Ponta Grossa - PR individuals attended at the University Laboratory of Clinical Analyses (LUAC) and in children participating in the Extension Project "Enteroparasitoses in Children of the Region of Ponta Grossa - PR". This cross-sectional retrospective study was carried out based on the analysis of the results of the coproparasitological examinations of these individuals, in the period from 2010 to 2016. A total of 5,630 coproparasitological exams were performed, of which 20.64% were positive, predominantly in women. The frequencies of positivity in the Extension Project and at the LUAC varied between 38.04% (2010) and 14.98% (2016), and 24.60% (2010) and 16.84% (2016), respectively. The most frequent species in the children attended by the extension project were Entamoeba coli (45.03%), Giardia duodenalis (34.80%) and Trichuris trichiura (17.68%) and in LUAC, Endolimax nana (52.63%), Entamoeba coli (38%) and Giardia duodenalis (15.75%). There was a decrease in the frequency of enteroparasites in the two groups studied, which demonstrates that the diagnosis, referral for treatment, when necessary, and supply of health education and prophylaxis actions are important, but the high prevalence of non-pathogenic protozoa (p<0.05) indicates problems of sanitation and food hygiene, making the transmission of pathogenic parasites to the population possible; although Ponta Grossa emerges in Brazil as the seventh most well-resourced municipality.